2015
DOI: 10.1038/srep12720
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4 acetylation required for chromatin decompaction during DNA replication

Abstract: Faithful DNA replication is a prerequisite for cell proliferation. Several cytological studies have shown that chromosome structures alter in the S-phase of the cell cycle. However, the molecular mechanisms behind the alteration of chromosome structures associated with DNA replication have not been elucidated. Here, we investigated chromatin structures and acetylation of specific histone residues during DNA replication using the meiotic nucleus of the fission yeast Schizosaccharomyces pombe. The S. pombe meiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 43 publications
2
22
0
3
Order By: Relevance
“…Such role may be similar to the one proposed for acetylated histones ( 63 , 64 ). In this regard, we observed that mutating four known acetylatable lysines of H2A.Z ( 55 , 60 ) to arginines ( pht1–4KR ) causes several defects ( Supplementary Figure S10 ); pht1–4KR mutation compromised DSB formation at the chromosome level and gene conversion frequency at ade6-M26 as much as pht1Δ , and reduced Rec10 levels at LinE sites more severely than pht1Δ .…”
Section: Discussionsupporting
confidence: 77%
“…Such role may be similar to the one proposed for acetylated histones ( 63 , 64 ). In this regard, we observed that mutating four known acetylatable lysines of H2A.Z ( 55 , 60 ) to arginines ( pht1–4KR ) causes several defects ( Supplementary Figure S10 ); pht1–4KR mutation compromised DSB formation at the chromosome level and gene conversion frequency at ade6-M26 as much as pht1Δ , and reduced Rec10 levels at LinE sites more severely than pht1Δ .…”
Section: Discussionsupporting
confidence: 77%
“…Strikingly, the presence of GFP-miniPR-Set7 SETmutant in Slimb/PR-Set7 RNAi treated cells was sufficient to maintain G1/S arrest and abnormal chromosomal compaction (Figure 6C ), suggesting that both phenotypes occur independently of PR-Set7 catalytic activity. Histone H4 acetylation is known to favor chromatin relaxation and DNA replication ( 4 , 40 , 41 ) and Drosophila PR-Set7 has been associated with histone deacetylase (HDAC) activity in chromatin assembly assays ( 42 ). We therefore hypothesized that the chromatin compaction and G1/S arrest phenotypes upon PR-Set7 stabilization could be related to changes in histone H4 acetylation induced by improper HDAC activity.…”
Section: Resultsmentioning
confidence: 99%
“…A well-known example is the balance exerted by the opposing action of histone H4 acetyltransferases (HAT) and deacetylases (HDAC) that modulates the levels of lysine acetylation on histone H4 and thus contributes to proper chromatin compaction during the cell cycle ( 3 ). Indeed, histone H4 acetylation is known to favor a more relaxed chromatin organization that is conducive to proper DNA replication initiation and S-phase progression ( 4 ). However, the mechanisms coordinating the activity of HAT and HDAC on histone H4 tail with the entry into S-phase still remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…H3K36me3 was chosen because its activity correlates with highly transcribed genes and is specifically down-regulated upon siRNA treatment of hnRNP L in HeLa cells (28). H4AcK8 plays a critical role in decompaction of chromatin structures during DNA replication (29) and was included as a test for euchromatinization of DNA. DNMT1, which transfers methyl groups to cytosine nucleotides of genomic DNA maintaining methylation patterns following DNA replication, was a general marker of gene activity (30).…”
Section: An Hnrnp L Variant and Irf1 Silence Ceacam1mentioning
confidence: 99%